A case of AIDS-associated Kaposi's sarcoma occurring in the oral cavity and systemic lymph nodes. Issue 4 (July 2022) - Nagano, Koki; Yamada, Tomohiro; Ishii, Kotaro; Fujinaga, Takahiro; Shibuya, Minami; Yanai, Yuta; Kiyoshima, Tamotsu; Mori, Yoshihide
Abstract: Kaposi's sarcoma (KS) is one of the most common malignancies in patients with acquired immunodeficiency syndrome (AIDS). KS is frequently detected in the skin, gastrointestinal tract and oral cavity, but rarely occurs in multiple systemic lymph nodes. Here, we report a case of AIDS-associated KS that occurred in both the oral region and multiple systemic lymph nodes. A 27-year-old man was referred to our department because of a mass in the oral cavity. The main clinical findings included multiple dark red masses in the oral cavity and generalized lymphadenopathy. Blood tests revealed infection with human immunodeficiency virus and human herpes virus 8. The histopathological diagnosis of both the oral masses and cervical lymph nodes was KS. After initiating antiretroviral therapy and chemotherapy with pegylated liposomal doxorubicin the lesions went into partial remission, and there was no sign of relapse 1 year later.